(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Uttarakhand, in recent times, has been a centre of much migration from the surrounding states, with immigrants pouring in, citing livelihood opportunities. As a result of the influx of various cultures, Uttarakhand’s plethora of crafts faces the perils of hybridization. Indigenous crafts of the region, due to increased migration, faces a syncretism of cultural influences resulting in alteration of design and practice as evident in the recent designs produced by Aipan artists or facing extinction like the craft of Dikara. Whereas, a number of initiatives have been introduced by the Union government to help artisans such as the Ambedkar Hastshilp Vikas Yojna, National Handicraft Development program, Handicrafts Mega Cluster Mission (HMCM), the beneficiaries are often unaware of these policies. To ensure the continuation of cultural practice, the initiatives need to be familiarized to the artisans to safeguard their interests in order to continue their practice and well-being. Considering the reference of Aipan practice in Uttarakhand, through discussions with artisans, craft and design experts, this study sought to understand and explore the existing conditions of artisans from Uttarakhand and their awareness on such initiations the government. This study further explores the need of such artisans and their subsequent suggestions on government initiations and help they covet for their well-being and sustenance of their craft practice.